(untitled) (The Pakistan Development Review, 2015)
Access to safe water is a basic need for human survival and health. Water is one of the most important commodities for households, who use it for drinking and many other important household activities including cooking a meal, washing dishes, bathing, laundry, cleaning, and watering the home gardens. Households need safe water and its availability on regular basis. Irregular and uncertain access to safe water affects not only these activities directly but also households’ health and workforce productivity indirectly. Thus, households give great importance to water, its quality and regular supply.